Brief Report: Increased Frequency of CD39+ CD56bright Natural Killer Cells in HIV-1 Infection Correlates With Immune Activation and Disease Progression. (1st April 2017) - Dierks, Patrick; Wroblewski, Raluca; Eberhard, Johanna M.; Martrus, Gloria; Degen, Olaf; Hertling, Sandra; Schmiedel, Stefan; Lunemann, Sebastian; Hüfner, Anja; Lohse, Ansgar W.; Altfeld, Marcus; van Lunzen, Jan; et al.
Abstract : Abstract: The expression pattern of the ectonucleotidases CD39 and CD73 on natural killer (NK) cells was examined in peripheral blood mononuclear cell of 61 HIV-1–infected patients. Increased frequencies of CD39 + CD56 bright NK cells were detectable in untreated HIV patients, which was associated with high viral load, low CD4 + T-cell count, and CD8 + T-cell activation. Additionally, levels of CD39 on NK cells were inducible by in vitro stimulation of NK cells, correlating with aryl hydrocarbon receptor and interleukin 10 expression. Here, we provide the first evidence of increased CD39 + CD56 bright NK cell frequencies during HIV infection, which might have consequences for NK cell function and HIV pathogenesis. Abstract : Supplemental Digital Content is Available in the Text.